Mother Tongue Interference : A study of Interlingual Errors in The Written Performance of the EFL Preparatory Year Female Students At Al-Baha University in Saudi Arabia - Al Shahrani, Hind Muget (Journal of Humanities & Social Sciences, 2018)
Language teachers have long recognized the phenomenon of native language influence on the learning of a second language. The present study attempted to investigate the effect of mother tongue interference in English writing essays of one hundred and twenty (120) English Foreign learners (EFL) Preparatory year. The study identified and categorized morphological errors according to surface structure taxonomy. The study then presented the influence of mother tongue interference (MTI) in the writing. The researcher used a comparative linguistics taxonomy model to identify the source of errors and both taxonomies by Dulay, Burt, & Krashen (1982). The questionnaire in this study was used to collect data support the results of the study, as well as to identify the weak points in participants writing skills. The findings revealed a variety of (lexical and grammatical) errors. The majority of errors were found to be attributed to free morpheme rather than bound morpheme. Omission errors were more frequent than other types of errors. Furthermore, the analyses of results showed statically significant effect between (MTI) and students’ interlingual errors. The study results include recommendations for the improvement of student’s performance in writing task/Based on results of study, some recommendations were included for improvement student’s performance writing skill.